Evaluation of Attitudes Towards Safe Use of Needle-Stick and Sharp Medical Instruments of Healthcare Workers in a Public Hospital - Eda Ağçay; Serap Ünsar (Sakarya Üniversitesi Holistik Sağlık Dergisi)
Objective: This cross-sectional and descriptive study was conducted to evaluate the attitudes of healthcare workers towards the safe use of needle-stick and sharp medical instruments.Methods: The study was conducted cross-sectionally on 248 healthcare workers. Data were collected face-to-face using the "Healthcare Worker Identification Form" and the "Healthcare Workers' Attitude Scale Towards Safe Use of Needle-Stick and Sharp Medical Instruments". Results: The total score and cognitive and affective subscale mean scores of the Attitudes Toward Safe Use of Needle-Stick and Sharp Medical Instruments Scale were statistically significantly higher in women than in men (p<0.05). The mean scores of healthcare workers who were having night shift were lower than those who were not having night shift (p<0.05). According to the results of linear regression analysis, gender, educational status, occupation, and exposure to injury were determined as factors independently affecting attitudes towards safe use of needle-stick and sharp medical instruments (p<0.05).Conclusion: In this study, it was found that the attitudes of male healthcare workers, those who were having night shift, those who experienced sharps injuries, midwives and health officers towards safe use of needle-stick and sharp medical instruments were low. In line with these results, it is recommended to organize in-service training programs for the prevention of sharps injuries, to pay attention to standard prevention practices and to actively use the reporting system, taking into account the personal (gender) and professional characteristics of healthcare workers (occupation, having a needle-stick and sharp injury, postgraduate education status, having night shift, etc.).